Linking environmental filtering and disequilibrium to biogeography with a community climate framework. Issue 4 (1st April 2015) - Blonder, Benjamin; Nogués-Bravo, David; Borregaard, Michael K.; Donoghue II, John C.; Jørgensen, Peter M.; Kraft, Nathan J. B.; Lessard, Jean-Philippe; Morueta-Holme, Naia; Sandel, Brody; Svenning, Jens-Christian; Violle, Cyrille; Rahbek, Carsten; et al.
Abstract : We present a framework to measure the strength of environmental filtering and disequilibrium of the species composition of a local community across time, relative to past, current, and future climates. We demonstrate the framework by measuring the impact of climate change on New World forests, integrating data for climate niches of more than 14 000 species, community composition of 471 New World forest plots, and observed climate across the most recent glacial–interglacial interval. We show that a majority of communities have species compositions that are strongly filtered and are more in equilibrium with current climate than random samples from the regional pool. Variation in the level of current community disequilibrium can be predicted from Last Glacial Maximum climate and will increase with near‐future climate change.